2021
DOI: 10.3389/fcell.2021.633607
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Hypoxia-Associated Prognostic Signature Related to Osteosarcoma Metastasis and Immune Infiltration

Abstract: BackgroundIncreasing evidence has shown that hypoxia microenvironment relates to tumor initiation and progression. However, no studies focus on the application of hypoxia-associated genes in predicting osteosarcoma patients’ prognosis. This research aims to identify the hypoxia-associated genes related to osteosarcoma metastasis and construct a gene signature to predict osteosarcoma prognosis.MethodsThe differentially expressed messenger RNAs (DEmRNAs) related to osteosarcoma metastasis were identified from Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…Patients with advanced non-small-cell lung cancer presenting with greater CD8 + T cell infiltration exhibit a superior treatment response to pembrolizumab, an anti-PD-1 drug ( Garon et al, 2019 ). Dendritic cells (DCs), which are antigen-presenting cells, often eliminate tumors by stimulating naive T cell differentiation ( Fu et al, 2021 ). HIF-1α inhibits plasmacytoid DC (pDC) differentiation, leading to tumor progression ( Labiano et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with advanced non-small-cell lung cancer presenting with greater CD8 + T cell infiltration exhibit a superior treatment response to pembrolizumab, an anti-PD-1 drug ( Garon et al, 2019 ). Dendritic cells (DCs), which are antigen-presenting cells, often eliminate tumors by stimulating naive T cell differentiation ( Fu et al, 2021 ). HIF-1α inhibits plasmacytoid DC (pDC) differentiation, leading to tumor progression ( Labiano et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more and more studies are involved. For example, in the nine studies (Cao et al, 2020;Chen Z. et al, 2020;Song et al, 2020;Wen et al, 2020;Xiao et al, 2020;Yu et al, 2020;Zhu et al, 2020;Fu et al, 2021;Yang et al, 2021) we included in the study based on the inclusion criteria, they all looked for potential survival-related OS gene signatures from public datasets.However, after we validated them in the training and validation cohorts, we found that the nine-gene signature we generated was superior to others in predicting OS prognosis. Among the nine studies, the one by Yang et al (2021)revealed a gene signature that closely resembled ours.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in cancer patient cohorts have similarly correlated the presence of hypoxia with an immunosuppressed TME in breast cancer, 45 , 46 clear cell renal cell carcinoma, 47 colorectal cancer, 48 hepatocellular carcinoma, 49–51 melanoma, 52 osteosarcoma, 53 neuroblastoma 43 and pancreatic cancer, 41 , 54 among others. 55 These studies used hypoxia gene signatures to determine the hypoxic state and immune fraction or gene set enrichment analysis to highlight the immune microenvironment.…”
Section: The Immune Contexture Of Hypoxic Tumors Remains Inconclusivementioning
confidence: 97%